Modified heterocyclic aramid fiber and preparation method thereof

By adjusting the rigid chain structure of the copolymer and controlling the polymerization reaction conditions, the elongation of the heterocyclic aramid fiber is improved, and its application limitations in high flexibility application scenarios are solved, achieving a wider market application.

CN119824567APending Publication Date: 2025-04-15SICHUAN PHAETON TECH CO LTD
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202510105439.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-23
Publication Date
2025-04-15

AI Technical Summary

Technical Problem

The low elongation of heterocyclic aramid fibers in breaking limits their application in applications requiring high flexibility, especially in products that combine with rubber.

Method used

By adjusting the rigid chain structure of the copolymer, using 2-(4-aminophenyl)-5-aminobenzimidazole, p-phenylenediamine, isophthalyl chloride and terephthalyl chloride as raw materials, and using LiCl as catalyst, modified heterocyclic aramid fibers were prepared in solvent polymerization, and the solid content of the reaction system and the polymerization reaction conditions were controlled to improve the elongation of the fibers in breakage.

Benefits of technology

Without increasing the production and manufacturing cost, the elongation of heterocyclic aramid fibers was successfully improved to ≥8%, expanding its market application in high flexibility application scenarios.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119824567A_ABST
    Figure CN119824567A_ABST
Patent Text Reader

Abstract

The invention discloses a modified heterocyclic aramid fiber and a preparation method thereof, and belongs to the technical field of high-performance organic fibers. The invention discloses a preparation method of a modified heterocyclic aramid fiber, which comprises the following steps: by taking 2-(4-aminophenyl)-5-aminobenzimidazole, p-phenylenediamine, isophthaloyl chloride and paraphthaloyl chloride as raw materials and LiCl as a catalyst, carrying out polymerization reaction in a solvent to obtain a polymer, and then spinning to obtain the modified heterocyclic aramid fiber. The invention also discloses the modified heterocyclic aramid fiber prepared by the method. According to the invention, m-phthaloyl chloride is creatively used for replacing a part of paraphthaloyl chloride and is subjected to nucleophilic reaction with 2-(4-aminophenyl)-5-aminobenzimidazole and p-phenylenediamine, so that the elongation at break of the fiber can be greatly improved under the condition that the breaking strength and other weather resistance of the original fiber are basically unchanged.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of high-performance organic fibers, and in particular relates to a modified heterocyclic aramid fiber and a preparation method thereof. Background Art

[0002] Heterocyclic aramid (aramid III fiber) is a type of para-aramid containing aromatic heterocycles in the main chain, and is typically represented by a structure containing a benzimidazole ring. According to theoretical calculations, the fiber formed by the ternary polycondensation of p-phenylenediamine, terephthaloyl chloride and benzimidazole diamine has a tensile strength of 4.5-5.5GPa and has extremely high thermal stability, with a decomposition temperature of up to 550°C. As a reinforcing material, the preparation of resin-based high-performance composite materials is one of the most important application areas of aramid, and is widely used in aerospace, military anti-ballistic, sports equipment, automobiles, construction and other fields.

[0003] However, since p-phenylenediamine and terephthaloyl chloride with rigid chain structures are used as the main raw materials in the polymerization production process, although heterocyclic aramid is given a higher tensile strength at break, it also leads to a lower elongation at break, usually not exceeding 4%. This low elongation at break limits its application in certain application scenarios, such as in rubber-bonded products that require high flexibility, such as conveyor belts, transport belts, and reinforced cords in tires. These applications require the material to have not only high strength, but also a certain degree of ductility to adapt to complex mechanical stress environments.

[0004] In summary, heterocyclic aramid is widely used in many high-tech fields due to its excellent mechanical properties and thermal stability. However, its low elongation at break limits its application in certain application scenarios that require high flexibility, especially in products combined with rubber, which places higher requirements on the comprehensive performance of the material. Therefore, providing a heterocyclic aramid fiber with higher elongation at break and better flexibility has become an urgent problem to be solved by those skilled in the art. Summary of the invention

[0005] One of the purposes of the present invention is to provide a method for preparing modified heterocyclic aramid fiber, which starts with the design of polymer molecular structure and improves the elongation at break of the finished fiber by adjusting the rigid chain structure of the copolymer, so as to obtain a heterocyclic aramid fiber product with an elongation at break ≥ 8% without increasing the production cost, thereby expanding the downstream application market of the product.

[0006] The second object of the present invention is to provide modified heterocyclic aramid fiber prepared by the method.

[0007] To achieve the above purpose, the technical solution adopted by the present invention is as follows:

[0008] The first aspect of the present invention discloses a method for preparing a modified heterocyclic aramid fiber, wherein the method uses 2-(4-aminophenyl)-5-aminobenzimidazole, p-phenylenediamine, isophthaloyl chloride, and terephthaloyl chloride as raw materials, uses LiCl as a catalyst, performs a polymerization reaction in a solvent to prepare a polymer, and then spins the polymer to obtain the modified heterocyclic aramid fiber;

[0009] The molar ratio of 2-(4-aminophenyl)-5-aminobenzimidazole to p-phenylenediamine is 2:0.8-1.2;

[0010] The mass ratio of terephthaloyl chloride to isophthaloyl chloride is 7-9:1-3;

[0011] During the reaction, the solid content of the system is controlled to be 3-7wt%.

[0012] In some embodiments of the present invention, the molar ratio of 2-(4-aminophenyl)-5-aminobenzimidazole to p-phenylenediamine is 2:1;

[0013] The mass ratio of terephthaloyl chloride to isophthaloyl chloride is 9:1;

[0014] During the reaction, the solid content of the system was controlled to be 5wt%.

[0015] In some embodiments of the present invention, the solvent comprises dimethylacetamide.

[0016] In some embodiments of the present invention, the method comprises the following steps:

[0017] Step 1. Prepolymerization reaction: 2-(4-aminophenyl)-5-aminobenzimidazole, p-phenylenediamine, isophthaloyl chloride and part of terephthaloyl chloride are subjected to prepolymerization reaction in a solvent under low temperature conditions under the catalytic action of LiCl;

[0018] Preferably, the reaction temperature is 1 to 6°C, more preferably 5°C;

[0019] Step 2. Telomerization reaction: according to the dynamic viscosity of the prepolymer reactant, the remaining terephthaloyl chloride is added to the polymerization reactor in batches for telomerization reaction; preferably, the telomerization reaction is carried out when the dynamic viscosity of the prepolymer reactant is 10,000 to 40,000 centipoise; preferably, the remaining terephthaloyl chloride is added to the polymerization reactor in 1 to 3 batches for telomerization reaction, and the total amount added is controlled not to exceed 102% of the theoretical weight; preferably, the telomerization reaction temperature is consistent with the prepolymerization reaction temperature;

[0020] Step 3. When the dynamic viscosity is 52,000 to 61,000 centipoise, the polymerized slurry is filtered and degassed, and then transferred to the spinning section to obtain modified heterocyclic aramid fibers.

[0021] In the present invention, terephthaloyl chloride is selected as the material added for telomerization because it is easier to disperse and dissolve in the reaction system, and its reaction state is more uniform and controllable.

[0022] In some embodiments of the present invention, the prepolymerization temperature is 30 to 40°C, preferably 35°C;

[0023] The prepolymerization reaction time is / is 30 to 120 min, preferably 60 min.

[0024] In some embodiments of the present invention, in the prepolymerization reaction, the feed amount of terephthaloyl chloride is 97-99% of its theoretical feed amount. The theoretical total feed amount of terephthaloyl chloride can be determined according to the solid content of the reaction system. Since the moisture content of terephthaloyl chloride varies between production batches, which affects the reaction activity, the prepolymerization feed amount is 97%-99%.

[0025] In some embodiments of the present invention, LiCl is first added to the solvent so that the content of LiCl (anhydrous lithium chloride) in the solvent system is about 3.5%.

[0026] In some embodiments of the present invention, the spinning section comprises the following steps:

[0027] S1. The spinning slurry is extruded through the spinning metering according to the design density specification and then enters the coagulation bath through the spinning assembly to form the primary fiber;

[0028] S2, the raw fiber is rolled up after washing and drying;

[0029] S3, the rewound raw fiber enters the two-stage heat treatment drying tunnel continuously through the unwinder and the traction roller;

[0030] S4, after stretching and forming, the finished fiber is obtained.

[0031] In some embodiments of the present invention, in S1, the coagulation liquid is an aqueous solution with a DMAC content of 45 to 55 wt %; preferably an aqueous solution with a DMAC content of 50 wt %;

[0032] In S2, the drying temperature is 130-140°C; preferably 135°C;

[0033] In S3, the first-stage heat treatment oven in the two-stage heat treatment oven has a front-to-back traction control stretching ratio of 0.8-1.2%, a front-to-back fiber tension of 45-55 cN, an oven temperature of 280-320°C, and an oven length of 10 meters; the front-to-back traction control stretching ratio of the second-stage heat treatment oven is 0.8-1.2%, a front-to-back fiber tension of 25-35 cN, an oven temperature of 420-470°C, an oven length of 10 meters, and a spinning speed of 18-22 m / min;

[0034] Preferably, the stretching ratio of the first-stage heat treatment oven is controlled by traction at 1%, the front and rear fiber tension is 50 cN, the oven temperature is 300°C, and the oven length is 10 meters. The stretching ratio of the second-stage heat treatment oven is controlled by traction at 2%, the front and rear fiber tension is 50 cN, the oven temperature is 450°C, the oven length is 10 meters, and the spinning speed is 20 m / min.

[0035] The second aspect of the present invention discloses a modified heterocyclic aramid fiber, which is prepared by the above method.

[0036] In some embodiments of the present invention, the elongation at break of the modified heterocyclic aramid fiber is ≥ 8%.

[0037] In the conventional polycondensation addition reaction process of heterocyclic aramid resin, isophthaloyl chloride (IPDC) is used to replace a part of terephthaloyl chloride (TPC) to carry out nucleophilic reaction with 2-(4-aminophenyl)-5-aminobenzimidazole (APBIA) and p-phenylenediamine (PPDA) to generate a new amide bond block structural unit. Due to the reduction of KEVLAR chain segments in the macromolecular chain structure, the fiber performance is reflected in the improvement of the breaking productivity. The reaction equation includes the following two block copolymerization reactions: 1.

[0039] 2.

[0041]

[0042] Compared with the prior art, the present invention has the following beneficial effects:

[0043] The invention is scientifically designed, ingeniously conceived, and creative. It uses isophthaloyl chloride (IPDC) to replace a part of terephthaloyl chloride (TPC) to carry out nucleophilic reaction with 2-(4-aminophenyl)-5-aminobenzimidazole (APBIA) and p-phenylenediamine (PPDA). It can greatly improve the elongation at break of the fiber while ensuring that the original fiber breaking strength and other weather resistance properties remain basically unchanged, so that the market application field of heterocyclic aramid fiber is expanded and the product quality is stable. The invention is of great significance to the development of the heterocyclic aramid fiber manufacturing industry and even the entire high-performance organic fiber manufacturing industry. BRIEF DESCRIPTION OF THE DRAWINGS

[0044] Attached Figure 1 It is a process flow chart of the present invention. DETAILED DESCRIPTION

[0045] The present invention is further described in detail below in conjunction with specific examples and verification of the pharmacological effects of the composition, which are intended to explain the present invention rather than to limit it. Where specific conditions are not specified in the embodiments, they are carried out under conventional conditions or conditions recommended by the manufacturer. Where the manufacturer of the reagents or instruments used is not specified, they are all conventional products that can be purchased commercially.

[0046] The "LiCl (anhydrous lithium chloride) content is about 3.5%" described in the embodiments of the present invention means that a total of 100 L of the solvent system contains 3.5 kg of anhydrous lithium chloride.

[0047] Example 1

[0048] This embodiment discloses a method for preparing heterocyclic aramid fiber, comprising the following steps:

[0049] S1. Add 390 L of DMAC (dimethylacetamide) solvent with a water content of 102 ppm into a 500 L polymerization kettle.

[0050] S2. Add 14.1 kg of LiCl (anhydrous lithium chloride) into the polymerization kettle containing the solvent to make the content of LiCl (anhydrous lithium chloride) in the solvent system about 3.5%.

[0051] S3. After stirring and dissolving in the polymerization kettle for 0.5 hour, according to the requirement of 5wt% solid content of the polymer material, the molar ratio of 2-(4-aminophenyl)-5-aminobenzimidazole (APBIA) to p-phenylenediamine (PPDA) is 2:1. The material addition amount is calculated by the reaction equation, and 9.41kg of 2-(4-aminophenyl)-5-aminobenzimidazole (APBIA) and 3.03kg of p-phenylenediamine (PPDA) are added into the polymerization kettle.

[0052] S4. Control the temperature at 35°C, stir and dissolve for 2 hours, then cool down to less than 5°C.

[0053] S5. According to the requirement of 5wt% solid content of the polymer material, the total amount of terephthaloyl chloride and isophthaloyl chloride is calculated by the reaction equation, and all the isophthaloyl chloride (IPDC) and terephthaloyl chloride (TPC) are added to the polymerization kettle in a mass ratio of 9:1 for prepolymerization.

[0054] S6. After stirring for 1 hour, according to the dynamic viscosity of the polymer reactant, the remaining theoretical total mass of terephthaloyl chloride (TPC), i.e., 0.186 kg, was added into the polymerization reactor in three portions to carry out telomerization reaction.

[0055] S7, sampling and testing, the dynamic viscosity is 58,000 centipoise.

[0056] S8. Filter and degas the polymerized slurry and then transfer it to the spinning section storage tank.

[0057] S9, the spinning slurry in the storage tank is extruded through spinning metering according to the linear density specification of 1000 dtex, and then enters the coagulation bath through the spinning assembly to form primary fibers. The coagulation liquid is an aqueous solution with a DMAC content of 50%.

[0058] S10, the spun fibers are rolled up after washing and drying. The washing water is deionized water and the drying temperature is 135°C.

[0059] S11. The reeled nascent fiber enters the two-stage heat treatment drying tunnel continuously through the unwinder and the traction roller. The first-stage heat treatment drying tunnel has a front and rear traction control stretching ratio of 1%, a front and rear fiber tension of 50cN, a drying tunnel temperature of 300℃, and a drying tunnel length of 10 meters. The second-stage heat treatment drying tunnel has a front and rear traction control stretching ratio of 2%, a front and rear fiber tension of 50cN, a drying tunnel temperature of 450℃, a drying tunnel length of 10 meters, and a spinning speed of 20 meters / minute.

[0060] S12. After stretching, 1 kg of finished fiber with a line density of 1023 dtex is obtained.

[0061] S13. The results of the test are shown in Table 1 below.

[0062] Table 1 Test results of modified heterocyclic aramid fiber of Example 1

[0063]

[0064] Example 2

[0065] This embodiment discloses a method for preparing heterocyclic aramid fiber, comprising the following steps:

[0066] S1. Add 390 L of DMAC (dimethylacetamide) solvent having a water content of 188 ppm into a 500 L polymerization reactor.

[0067] S2. Add LiCl (anhydrous lithium chloride) with a weight of 14.1 kg into the polymerization kettle containing the solvent, that is, the content of LiCl (anhydrous lithium chloride) in the solvent system is about 3.5%.

[0068] S3. After stirring and dissolving in the polymerization kettle for 0.5 hour, according to the requirement of 5wt% solid content of the polymer material, the molar ratio of 2-(4-aminophenyl)-5-aminobenzimidazole (APBIA) to p-phenylenediamine (PPDA) is 2:1. The material addition amount is calculated by the reaction equation, and 9.41kg of 2-(4-aminophenyl)-5-aminobenzimidazole (APBIA) and 3.03kg of p-phenylenediamine (PPDA) are added into the polymerization kettle.

[0069] S4. Control the temperature at 35°C, stir and dissolve for 2 hours, then cool down to less than 5°C.

[0070] S5. According to the requirement of 5wt% solid content of the polymer material, the total amount of terephthaloyl chloride and isophthaloyl chloride is calculated by the reaction equation, and all isophthaloyl chloride (IPDC) and terephthaloyl chloride (TPC) are added to the polymerization kettle in a mass ratio of 8:2 to carry out prepolymerization reaction.

[0071] S6. After stirring for 1 hour, according to the dynamic viscosity of the polymer reactant, the remaining theoretical total mass of terephthaloyl chloride (TPC), i.e., 0.165 kg, was added into the polymerization reactor in three portions to carry out telomerization reaction.

[0072] S7, sampling and testing, the dynamic viscosity is 61,000 centipoise.

[0073] S8. Filter and degas the polymerized slurry and then transfer it to the spinning section storage tank.

[0074] S9, the spinning slurry in the storage tank is extruded through spinning metering according to the linear density specification of 1000 dtex, and then enters the coagulation bath through the spinning assembly to form primary fibers. The coagulation liquid is an aqueous solution with a DMAC content of 50%.

[0075] S10, the spun fibers are rolled up after washing and drying. The washing water is deionized water and the drying temperature is 135°C.

[0076] S11. The reeled nascent fiber enters the two-stage heat treatment drying tunnel continuously through the unwinder and the traction roller. The first-stage heat treatment drying tunnel has a front and rear traction control stretching ratio of 1%, a front and rear fiber tension of 50cN, a drying tunnel temperature of 300℃, and a drying tunnel length of 10 meters. The second-stage heat treatment drying tunnel has a front and rear traction control stretching ratio of 1%, a front and rear fiber tension of 30cN, a drying tunnel temperature of 450℃, a drying tunnel length of 10 meters, and a spinning speed of 20 meters / minute.

[0077] S12. After stretching, 1 kg of finished fiber with a line density of 1041 dtex is obtained.

[0078] S13. The results of the test are shown in Table 2 below.

[0079] Table 2 Test results of modified heterocyclic aramid fiber of Example 2

[0080]

[0081] Example 3

[0082] This embodiment discloses a method for preparing heterocyclic aramid fiber, comprising the following steps:

[0083] S1. Add 390 L of DMAC (dimethylacetamide) solvent having a water content of 188 ppm into a 500 L polymerization reactor.

[0084] S2. Add 14.1 kg of LiCl (anhydrous lithium chloride) into the polymerization kettle containing the solvent to make the content of LiCl (anhydrous lithium chloride) in the solvent system about 3.5%.

[0085] S3. After stirring and dissolving in the polymerization kettle for 0.5 hour, according to the requirement of 5wt% solid content of the polymer material, the molar ratio of 2-(4-aminophenyl)-5-aminobenzimidazole (APBIA) to p-phenylenediamine (PPDA) is 2:1. The material addition amount is calculated by the reaction equation, and 9.41kg of 2-(4-aminophenyl)-5-aminobenzimidazole (APBIA) and 3.03kg of p-phenylenediamine (PPDA) are added into the polymerization kettle.

[0086] S4. Control the temperature at 35°C, stir and dissolve for 2 hours, then cool down to less than 5°C.

[0087] S5. According to the requirement of 5wt% solid content of the polymer material, the total amount of terephthaloyl chloride and isophthaloyl chloride is calculated by the reaction equation, and all isophthaloyl chloride (IPDC) and terephthaloyl chloride (TPC) are added to the polymerization kettle in a mass ratio of 7:3 for prepolymerization.

[0088] S6. After stirring for 1 hour, according to the dynamic viscosity of the polymer reactant, the remaining theoretical total mass of terephthaloyl chloride (TPC), i.e., 0.145 kg, was added into the polymerization reactor in three portions to carry out telomerization reaction.

[0089] S7, sampling and testing, the dynamic viscosity is 52,000 centipoise.

[0090] S8. Filter and degas the polymerized slurry and then transfer it to the spinning section storage tank.

[0091] S9, the spinning slurry in the storage tank is extruded through spinning metering according to the linear density specification of 1000 dtex, and then enters the coagulation bath through the spinning assembly to form primary fibers. The coagulation liquid is an aqueous solution with a DMAC content of 50%.

[0092] S10, the spun fibers are rolled up after washing and drying. The washing water is deionized water and the drying temperature is 135°C.

[0093] S11. The reeled nascent fiber enters the two-stage heat treatment drying tunnel continuously through the unwinder and the traction roller. The first-stage heat treatment drying tunnel has a front and rear traction control stretching ratio of 1%, a front and rear fiber tension of 50cN, a drying tunnel temperature of 300℃, and a drying tunnel length of 10 meters. The second-stage heat treatment drying tunnel has a front and rear traction control stretching ratio of 1%, a front and rear fiber tension of 30cN, a drying tunnel temperature of 450℃, a drying tunnel length of 10 meters, and a spinning speed of 20 meters / minute.

[0094] S12. After stretching, 1 kg of finished fiber with a line density of 1011 dtex is obtained.

[0095] S13. The results of the test are shown in Table 3 below.

[0096] Table 3 Test results of modified heterocyclic aramid fiber of Example 3

[0097]

[0098] Comparative Example 1

[0099] In this embodiment, a general heterocyclic aramid fiber production process is used for implementation, including the following steps:

[0100] S1. Add 390 L of DMAC (dimethylacetamide) solvent having a water content of 188 ppm into a 500 L polymerization reactor.

[0101] S2. Add LiCl (anhydrous lithium chloride) with a weight of 14.1 kg into the polymerization kettle containing the solvent, that is, the content of LiCl (anhydrous lithium chloride) in the solvent system is about 3.5%.

[0102] S3. After stirring and dissolving in the polymerization kettle for 0.5 hour, according to the requirement of 5wt% solid content of the polymer material, the molar ratio of 2-(4-aminophenyl)-5-aminobenzimidazole (APBIA) to p-phenylenediamine (PPDA) is 2:1. The material addition amount is calculated by the reaction equation, and 9.41kg of 2-(4-aminophenyl)-5-aminobenzimidazole (APBIA) and 3.03kg of p-phenylenediamine (PPDA) are added into the polymerization kettle.

[0103] S4. Control the temperature at 35°C, stir and dissolve for 2 hours, then cool down to less than 5°C.

[0104] S5. According to the requirement of 5wt% solid content of the polymer material, the total amount of terephthaloyl chloride added is calculated by the reaction equation, and 98.5% of the theoretical total mass of terephthaloyl chloride (TPC), i.e. 13.582 kg, is added into the polymerization kettle for prepolymerization.

[0105] S6. After stirring for 1 hour, according to the dynamic viscosity of the polymer reactant, the remaining theoretical total mass of terephthaloyl chloride (TPC), i.e., 0.207 kg, was added into the polymerization reactor in three portions to carry out telomerization reaction.

[0106] S7, sampling and testing, the dynamic viscosity is 80,000 centipoise.

[0107] S8. Filter and deaerate the spinning slurry and then transfer it to the spinning section storage tank.

[0108] S9, the spinning slurry in the storage tank is extruded through spinning metering according to the linear density specification of 1000 dtex, and then enters the coagulation bath through the spinning assembly to form primary fibers. The coagulation liquid is an aqueous solution with a DMAC content of 50%.

[0109] S10, the spun fiber is then washed and dried before being rolled up. The washing water is deionized water and the drying temperature is 135°C.

[0110] S11. The spun fibers after winding are continuously fed into a two-stage heat treatment drying tunnel through an unwinder and traction rollers. The stretching ratio of the first-stage heat treatment drying tunnel is controlled by traction at 1%, the front and rear fiber tension is 50 cN, the drying tunnel temperature is 300°C, and the drying tunnel length is 10 meters. The stretching ratio of the second-stage heat treatment drying tunnel is controlled by traction at 1%, the front and rear fiber tension is 30 cN, the drying tunnel temperature is 450°C, the drying tunnel length is 10 meters, and the spinning speed is 20 m / min.

[0111] S12. After stretching, 1 kg of finished fiber with a line density of 1011 dtex is obtained.

[0112] S13. The results of the test are shown in Table 4 below.

[0113] Table 4 Comparative Example Heterocyclic Aramid Fiber Test Results

[0114]

[0115] The data of the embodiments and comparative examples are summarized in Table 5.

[0116] Table 5 Comparison of heterocyclic aramid fiber test results of the embodiment and the comparative example

[0117]

[0118] It can be seen from the above data that the breaking productivity of the ZI fiber, a modified structural product of heterocyclic aramid fiber of the present invention, is ≥8.0%, which is more than double the breaking elongation of 4% of the general heterocyclic aramid fiber.

[0119] In the product polymerization production process, only part of the isophthaloyl chloride raw material is introduced to replace the terephthaloyl chloride raw material, and the other process methods remain unchanged. In addition, the production of isophthaloyl chloride is easier to prepare and its price is lower than that of terephthaloyl chloride. In the spinning process, only the drying oven stretching ratio is reduced, and the other process methods remain unchanged. This makes the fiber less likely to produce lint and the product appearance is neat, which is of great value in improving the differentiated product types of heterocyclic aramid and stabilizing product quality.

[0120] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for preparing a modified heterocyclic aramid fiber, characterized in that: Using 2-(4-aminophenyl)-5-aminobenzimidazole, p-phenylenediamine, isophthaloyl chloride and terephthaloyl chloride as raw materials and LiCl as catalyst, a polymer is prepared by polymerization reaction in a solvent, and then spinning is performed to obtain a modified heterocyclic aramid fiber; The molar ratio of 2-(4-aminophenyl)-5-aminobenzimidazole to p-phenylenediamine is 2:0.8-1.2; The mass ratio of terephthaloyl chloride to isophthaloyl chloride is 9:0.8-1.2; During the reaction, the solid content of the system is controlled to be 3-7wt%.

2. The method for preparing a modified heterocyclic aramid fiber according to claim 1, characterized in that: The molar ratio of 2-(4-aminophenyl)-5-aminobenzimidazole to p-phenylenediamine is 2:1; The mass ratio of terephthaloyl chloride to isophthaloyl chloride is 7-9:1-3; During the reaction, the solid content of the system was controlled to be 5wt%.

3. The method for preparing a modified heterocyclic aramid fiber according to claim 1 or 2, characterized in that: The solvent includes dimethylacetamide.

4. A method for preparing a modified heterocyclic aramid fiber according to claim 1 or 2, characterized in that: The steps include: Step 1. Prepolymerization reaction: 2-(4-aminophenyl)-5-aminobenzimidazole, p-phenylenediamine, isophthaloyl chloride and part of terephthaloyl chloride are subjected to prepolymerization reaction in a solvent under low temperature conditions under the catalytic action of LiCl; Preferably, the reaction temperature is 1 to 6°C, more preferably 5°C; Step 2. Telomerization reaction: according to the dynamic viscosity of the prepolymer reactant, the remaining terephthaloyl chloride is added to the polymerization reactor in batches for telomerization reaction; preferably, the telomerization reaction is carried out when the dynamic viscosity of the prepolymer reactant is 10,000 to 40,000 centipoise; preferably, the remaining terephthaloyl chloride is added to the polymerization reactor in 1 to 3 batches for telomerization reaction, and the total amount added is controlled not to exceed 102% of the theoretical weight; preferably, the telomerization reaction temperature is consistent with the prepolymerization reaction temperature; Step 3. When the dynamic viscosity is 52,000 to 61,000 centipoise, the polymerized slurry is filtered and degassed, and then transferred to the spinning section to obtain modified heterocyclic aramid fibers.

5. The method for preparing a modified heterocyclic aramid fiber according to claim 4, characterized in that: The prepolymerization temperature is 30-40°C, preferably 35°C; The prepolymerization reaction time is / is 30 to 120 min, preferably 60 min.

6. The method for preparing a modified heterocyclic aramid fiber according to claim 4, characterized in that: In the prepolymerization reaction, the feeding amount of terephthaloyl chloride is 97-99% of its theoretical feeding amount.

7. The method for preparing a modified heterocyclic aramid fiber according to claim 4, characterized in that: The spinning section comprises the following steps: S1. The spinning slurry is extruded through the spinning metering according to the design density specification and then enters the coagulation bath through the spinning assembly to form the primary fiber; S2, the raw fiber is rolled up after washing and drying; S3, the rewound raw fiber enters the two-stage heat treatment drying tunnel continuously through the unwinder and the traction roller; S4, after stretching and forming, the finished fiber is obtained.

8. The method for preparing a modified heterocyclic aramid fiber according to claim 7, characterized in that: In S1, the coagulation liquid is an aqueous solution with a DMAC content of 45 to 55 wt %, preferably an aqueous solution with a DMAC content of 50 wt %; In S2, the drying temperature is 130-140°C; preferably 135°C; In S3, the first-stage heat treatment oven in the two-stage heat treatment oven has a front-to-back traction control stretching ratio of 0.8-1.2%, a front-to-back fiber tension of 45-55 cN, an oven temperature of 280-320°C, and an oven length of 10 meters; the front-to-back traction control stretching ratio of the second-stage heat treatment oven is 0.8-1.2%, a front-to-back fiber tension of 25-35 cN, an oven temperature of 420-470°C, an oven length of 10 meters, and a spinning speed of 18-22 m / min; Preferably, the stretching ratio of the first-stage heat treatment oven is controlled by traction at 1%, the front and rear fiber tension is 50 cN, the oven temperature is 300°C, and the oven length is 10 meters. The stretching ratio of the second-stage heat treatment oven is controlled by traction at 2%, the front and rear fiber tension is 50 cN, the oven temperature is 450°C, the oven length is 10 meters, and the spinning speed is 20 m / min.

9. A modified heterocyclic aramid fiber, characterized in that: The method is prepared by the method described in any one of claims 1 to 8.

10. The modified heterocyclic aramid fiber according to claim 9, characterized in that: The elongation at break of the modified heterocyclic aramid fiber is ≥8%.

Citation Information

Cited By

  • Modified aramid fiber based on polyamide solution containing heterocyclic monomer and preparation method of modified aramid fiber

    CN121451313A

  • Modified aramid based on polyamide solution containing heterocyclic monomer and preparation method thereof

    CN121451313B